Regulatory Impact Analysis Roles for Agricultural Products’ Qualities: Customers’ Perspectives for Sustainability Entrepreneurship - Abdullah, Zulhamri; Yusoff , Wan Fauziah Wan; Anumudu, Chinedu Eugenia; Zainol, Fakhrul Anwar (Asian Journal of Agriculture and Rural Development, 2020)
The purpose of this study is to contribute to the emerging agro- entrepreneurship empirical literature from the Malaysian regulatory impact analysis context. Therefore, this study explicitly provides an empirical analysis of the regulatory impact assessment based on consumers’ perceptions. In line with the purpose of the study, we applied a quantitative approach through a survey questionnaire for the aim of generating data from the central, south, and east coast Malaysian consumers’ opinions. Consequently, we found that the majority of the respondents had little knowledge of the impact of grading, packaging, and labelling (GPL). Furthermore, the study established that over two-thirds of the customers always check the label of the products they intend to purchase. The majority of the consumers were also concerned with the Halal label when purchasing products.